Antiarthritic Activity of Pergularia daemia [Forsk] Leaf Extracts on Experimental Animals - Sutar N. G. (Current Approaches in Science and Technology Research Vol. 7, 2021)
Objective: Pergularia daemia [Forsk] has been used from long time in traditional medicine. The main objective of this work is to evaluate anti-rheumatic activity of leaf of Pergularia daemia [Forsk] Methods: Anti- arthritic activity of petroleum ether and methanol extracts of leaf of Pergularia daemia [Forsk] was evaluated by using Freund’s complete adjuvant model. Results: Preliminary Phytochemical investigation of Petroleum ether extract of leaf of Pergularia daemia [Forsk] shows presence of steroids, terpenoids, sterols while methanolic extract of leaf of Pergularia daemia [Forsk] shows presence of alkaloids, glycosides, flavonoids, tannins and phenolic component. The petroleum ether extract [300 mg / kg] shows. Conclusion: The methanolic extract was found to be more potent than petroleum ether extract. The result indicate that the petroleum ether and methanol extract contain such phytochemical constituents which are responsible for analgesic and anti-rheumatic activity.